Development Of Coastal Sediment Database - Nur Azlin Atikah Mohd Nasir; Nursuhaila Muhamad Fauzi; Aimie Rifhan Hashim; Sharir Aizat Kamaruddin (Malaysia Journal of Invention and Innovation)
Sediment is a naturally occurring material that is broken down by weathering and erosion and then moved by the action of wind, water, or ice, or by gravity acting on the particles. Presently, data are scarce regarding the specific attributes of sediment found along the coast, particularly in the northern area of Peninsular Malaysia. The databases provide data on sediment pH, moisture content, particle size, and organic matter. The database would facilitate efficient management of coastal area development for government sectors and industry stakeholders. Sampling activities included collecting samples of beach and paddy field sediments. The development of the coastal sediment database is consistent with the Sustainable Development Goals established by the United Nations which include SDG 14: "Life below water," SDG 2: "Zero hunger," SDG 3: "Good health and well-being," and SDG 13: "Climate action".